GP282 An evaluation of the normal ranges of exercise tolerance in healthy children and adolescents as measured by the modified shuttle test (MST). (June 2019) - Corley, LM; Canny, S; O'Connor, L; Lynn, M; O'Neill, MB
Abstract : Aim: The aim of this study was to utilise the Modified Shuttle Test (MST) to determine the exercise capacity range of Irish children and adolescents 5 to 15 years of age. The MST is a well defined test, administered by a trained physiotherapist, following the protocol described by LaLeger. Methods: Children and Adolescents 5–15 years of age with negative bronchial reactivity testing and an absence of underlining chronic respiratory or cardiac disease were eligible for inclusion. The MST has 15 levels, each lasting 1 minute, with incremental increases in speed of 0.61 km/h each minute. The test requires participants to move between two markers, which are 10 metres apart, in time with the beeps from a pre-recorded digital audio track. The test is halted if the participant is unable to continue or fails to reach the 10 meter mark on two consecutive beeps. The test takes on average 25 minutes to complete. Results: Data was available on 277 children with negative bronchial reactivity. The M;F was 1.27:1. The mean age was 10 years old (range 5–15).The number of patients per age in years ranged from 14 to 33 (mean 25). The line of best fit indicates that the mean exercise distance reached in meters was given by the formula Y = (54.7×Age) + 404. The study noted that the main reasons for test cessation related to fatigue and shortness of breath. Conclusions: This study defines normative data for children's exercise capacity as measured by the MST. It provides a frame of reference for parents in discussing their child's exercise tolerance and the modified formula is easy to use (distance travelled = 55x Age + 400m).